Adorno's gamble : harnessing German ideology - Immanen, Mikko, 1982- (Ithaca, New York : Cornell University Press and Cornell University Library, 2025)
"The book reinterprets the thought of Theodor W. Adorno, the leading light of the Frankfurt School and one of the most influential leftist intellectuals of the twentieth century, by arguing that his worries over the frailty of reason and democracy were inspired by radical conservative thinkers of Weimar Germany"--
Introduction : Repurposing Zivilisationskritik for Progressive Ends -- Adorno's Klages Project : The Origin of Negative Dialectics -- "Caesarism" : Spengler's Master Class in Democracy's Self-Destruction -- "Demystification of Antiquity" : Dialectic of Enlightenment -- Epilogue : Legacies of Adorno's Gamble.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 13, 2025).
JSTOR
Keywords: Adorno, Theodor W., -- 1903-1969.; Spengler, Oswald, -- 1880-1936 -- Influence; Klages, Ludwig, -- 1872-1956 -- Influence; Philosophy, German -- 20th century; Frankfurt school of sociology; Philosophie allemande -- 20e siècle.; École de Francfort (Sociologie); LITERARY CRITICISM / European / German; Electronic books